2018
DOI: 10.1373/clinchem.2017.272443
|View full text |Cite
|
Sign up to set email alerts
|

Role of Physical Activity and Exercise in Treating Patients with Overweight and Obesity

Abstract: The literature supports the inclusion of physical activity as an important lifestyle behavior for regulating body weight. There are multiple intervention approaches that may be effective for enhancing physical activity engagement within the context of weight control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
89
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(97 citation statements)
references
References 72 publications
2
89
0
6
Order By: Relevance
“…Physical activity is an important non-pharmacological intervention for managing chronic lifestyle-related diseases, such as obesity and diabetes. While the beneficial effects of exercise are well documented and evidence indicates that regular exercise is a viable, cost effective but underused treatment [11], the related molecular mechanisms are not yet fully understood [12,13]. Reports addressing circulating concentrations of EPHX2 and its metabolites in response to exercise in humans are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity is an important non-pharmacological intervention for managing chronic lifestyle-related diseases, such as obesity and diabetes. While the beneficial effects of exercise are well documented and evidence indicates that regular exercise is a viable, cost effective but underused treatment [11], the related molecular mechanisms are not yet fully understood [12,13]. Reports addressing circulating concentrations of EPHX2 and its metabolites in response to exercise in humans are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, participants were least willing, on average, to pursue physical activity targets. Given the importance of physical activity for weight management (Jakicic, Rogers, Davis, & Collins, ), additional design efforts may be needed to inform how to engage users in these goals.…”
Section: Discussionmentioning
confidence: 99%
“…Recently obesity and overweight prevalence has increased in many industrial countries, making it depressing for many populations. It is reported that more particularly in developing countries along with the developing level of welfare and domestic income, reasons such as changes in nutrition habits of individuals and insufficient physical activities increase the level of obesity [4] [40] [41] [42]. This study backs up this report as it shows that subjects have healthy lifestyle behaviors with low rates of 3.4% for regular physical activity, 26.0% for health responsibility and 38.4% for regular nutrition habits ( Table 5).…”
Section: Discussionmentioning
confidence: 99%